Manajemen Lembaga Pendidikan Islam - Yaqin, Nurul (MADINAH, 2016)
Education is a very important thing in human life. The advancement of a nation depends on the nation's education. This means that if the education of a nation can produce a quality human is born inward. Automatically the nation will progress, peace and tetram. Conversely, if the education of a nation stagnated then the nation will be retarded in all fields. Islamic education institutions to date have not been able to map the problems that must be faced. As a result, the development of Islamic education is not encouraging and has not fulfilled the ideal ideals, namely to produce fully-equipped people, not only in the religious field. "The eyes must be opened that there are problems that must be faced to move forward," said Prof. Dr. Abuddin Nata MA in his inauguration speech as a professor of history and philosophy of Islamic education at the Faculty of Tarbiyah and the State Islamic University (UIN) Syarif Hidayatullah Jakarta Problems that arise and must be faced now, said Abuddin, including the rapid development of technology that affects the entire field. While on the other hand, educational institutions have not been able to respond.